Ozma of Oz.. - Baum, L. Frank (Lyman Frank), 1856-1919; Neill, John R. (John Rea); Reilly & Britton Co. (Chicago : The Reilly & Britton Co., 1907)
When a storm blows Dorothy to the land of Ev where lunches grow on trees, she meets the Scarecrow, the Tin Woodman, the Cowardly Lion, and Princess Ozma, and together they set out to free the Queen of Ev and her ten children imprisoned by the Nome King.
The girl in the chicken coop -- The yellow hen -- Letters in the sand -- Tiktok, the machine man -- Dorothy opens the dinner pail -- The heads of Langwidere -- Ozma of Oz to the rescue -- The hungry tiger -- The royal family of Ev -- The giant with the hammer -- The Nome King -- The eleven guesses -- The Nome King laughs -- Dorothy tries to be brave -- Billina frightens the Nome King -- Purple, green and gold -- The Scarecrow wins the fight -- The fate of the Tin Woodman -- The King of Ev -- The Emerald City -- Dorothy's magic belt.
Illustrated end-papers in colors.
Greene & Hanff. Bibliographia Oziana (revised and expanded edition)
Mode of access: Internet.
Keywords: Princess Ozma -- (Fictitious character) -- Juvenile fiction; Tin Woodman -- (Fictitious character) -- Juvenile fiction; Cowardly Lion -- (Fictitious character) -- Juvenile fiction; Scarecrow -- (Fictitious character from Baum) -- Juvenile fiction; Gale, Dorothy -- (Fictitious character) -- Juvenile fiction; Oz (Imaginary place) -- Juvenile fiction; Juvenile works; Fiction; Fantasy fiction; Novels; Juvenile literature -- 1907.; Novels; Children's stories; Fantasy fiction; Juvenile works; Fiction